The time for austerity: Estimating the average treatment effect of fiscal policy - Òscar Jordà; Alan M. Taylor (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
After the Global Financial Crisis a controversial rush to fiscal austerity followed in many countries. Yet research on the effects of austerity on macroeconomic aggregates was and still is unsettled, mired by the difficulty of identifying multipliers from observational data. This paper reconciles seemingly disparate estimates of multipliers within a unified and state-contingent framework. We achieve identification of causal effects with new propensity-score based methods for time series data. Using this novel approach, we show that austerity is always a drag on growth, and especially so in depressed economies: a one percent of GDP fiscal consolidation translates into 4 percent lower real GDP after five years when implemented in the slump rather than the boom. We illustrate our findings with a counterfactual evaluation of the impact of the U.K. government's shift to austerity policies in 2010 on subsequent growth.
urn:nbn:de:hebis:30:3-361387
Keywords: C54; C99; E32; E62; H20; H5; N10; 330; Rubin Causal Model; allocation bias; average treatment effect; booms; fiscal multipliers; identification; inverse probability weighting; local projection; matching; output fluctuations; propensity score; regression adjustment; slumps